Characterization, dissolution and in vivo evaluation of solid acetazolamide complexes - Mora, Maria Julia (2013)
The effects of binary and ternary systems of acetazolamide (ACZ) with hydroxypropyl-β-cyclodextrin (HP-β-CD) alone or with triethanolamine (TEA) on the crystalline properties, dissolution and intraocular pressure (IOP)-lowering effect were investigated. It was found that the crystal structure of ACZ powder could be modified by the processing conditions. Freeze-drying ACZ powder affected not only the particle morphology but also its polymorphic form and the starting ACZ was converted to pure form A upon freeze-drying treatment. Results provided by DSC/TGA, XRPD, SEM and FT-IR suggested the formation of inclusion complexes between ACZ with HP-β-CD alone or with TEA, obtained by the freeze-drying method and the conversion of the drug into the amorphous state. Binary and ternary systems of ACZ obtained by freeze-drying exhibited significantly enhanced ACZ dissolution rates. The IOP-lowering effects of ACZ and its complexes with HP-β-CD alone or with TEA were studied in normotensive rabbits. Whereas the maximum IOP-lowering effect (∼4 mmHg, ∼33%), obtained with these binary and ternary lyophilized ACZ systems occurred at around 90 min, the ternary system exhibited a longer maximum IOP-lowering effect peak compared with that of the binary system. These results are in line with those obtained from the dissolution studies, where the ternary system exhibited longer dissolution times compared to the lyophilized binary one. Results obtained from the dissolution studies, also showed that freeze-drying the native crystalline form of ACZ significantly increased the dissolution rate of ACZ, thus improving the IOP-lowering effect of this drug.